The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages made to find workers who could do the jobs, and not to find congenial jobs for the workers, but much experience has been gained and we must see that after the war this is used to enable workers to find jobs in which they can develop their particular inclinations. Another new responsibility the Ministry has assumed is the placing in employment of disabled persons. This applies not only to war casualties but to other people unable to compete with normal people in seeking work. At present the procedure is that a form, R.D.1. is completed by the hospital for any patient who is unfit to return to his old work whether on account of injury sustained in any way or on account of an illness such as tuberculosis, gastric ulcer, rheumatism, etc., which necessitates special care in the choice of work. There is an Officer attached to each Labour Exchange who pays periodical visits to the hospital to see any patients for whom forms have been completed. The officer discusses future work both with the patient and the doctor and after the interview his comments and the form are sent to the local Exchange. The weakness of the scheme lies in the fact that it depends too much upon the interest and the initiative of the appropriate officers of the Labour Exchange, many of whom have had no special training and do not know either the implications of a patient's disability or the full range of occupations available in industry 27 15X/2/464/1